Determinación de la sustentabilidad mediante indicadores Socio-Económicos y Ambientales de Salache, Parroquia Eloy Alfaro, Cantón Latacunga, Provincia de Cotopaxi, 2017 - Mera Vizcaíno, Franklin Leonel (2018)
The research was conducted in the sector of Salache, in the neighborhoods Salache Alto and Salache Rumipamba, consists of a population of 300 inhabitants, where its economy is generated by agriculture and the external work of its inhabitants, the soils of the sector are loamy in the high and sandy loam in the lower part with strong erosion processes, the type of research used was descriptive, exploratory, qualitative-quantitative, analytical and explanatory - not experimental. The information was based on diverse sources including surveys and interviews working with a sample of 170, where 45 qualitative and quantitative variables were analyzed in the characterization and 24 indicators of Socio-Economic and Environmental sustainability of the sector of Salache. The relationships established between the biophysical, agronomic and technological components associated with the agricultural subsystems were evaluated using descriptive statistics techniques. In the characterization it was determined that the community under study has 24% illiteracy, which does not allow socioeconomic and environmental development in the area. It was determined that 88% of the surveyed sample has not received any type of training from governmental and non-governmental entities. The biggest responsibilities in the management of the production units are in charge of women in 66% and for men 34%. In the sector of Salache, 100% the population does not have a medical center near, and they have to travel half an hour by car to be served, this makes the farmer lose time and money in mobility with high risk with his life in Emerging cases. The type of agriculture that the sector has is 88% organic and 12% conventional. The activities to which dedicated are to agriculture with 89%, followed by livestock with 9% and the commercialization of agricultural products with 2%, which demonstrates the importance that should be given to the agricultural situation focusing on soil problems, crop management and marketing, with the aim of improving the socioeconomic situation of the area. In the characterization carried out it was possible to determine that 56% of the population have irrigation water and 44% do not have a limiting factor for agricultural production. In the evaluation of sustainability it was possible to determine that in the economic dimension the value of 1.75 was determined; in the social dimension the value of 1.85 was obtained and the Environmental dimension of 2.21 determining the general sustainability 1.89, which indicates that the production units of Salache are not sustainable.